2011
DOI: 10.1038/hdy.2011.74
|View full text |Cite
|
Sign up to set email alerts
|

Co-localisation of host plant resistance QTLs affecting the performance and feeding behaviour of the aphid Myzus persicae in the peach tree

Abstract: The architecture and action of quantitative trait loci (QTL) contributing to plant resistance mechanisms against aphids, the largest group of phloem-feeding insects, are not well understood. Comparative mapping of several components of resistance to the green peach aphid (Myzus persicae) was undertaken in Prunus davidiana, a wild species related to peach. An interspecific F 1 population of Prunus persica var. Summergrand  P. davidiana clone P1908 was scored for resistance (aphid colony development and foliar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…No evidence was found in the EPG experiments for antixenotic resistance in the resistant cultivar and resistant NIL; however, a possible antibiosis‐type resistance could be present but work in a delayed manner, and would therefore not be detected in the short‐term EPG experiments as was hypothesized by Sauge et al. ().…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…No evidence was found in the EPG experiments for antixenotic resistance in the resistant cultivar and resistant NIL; however, a possible antibiosis‐type resistance could be present but work in a delayed manner, and would therefore not be detected in the short‐term EPG experiments as was hypothesized by Sauge et al. ().…”
Section: Discussionmentioning
confidence: 86%
“…Another explanation could be that Nr-resistance exerts an antibiotic effect on free-living aphids. No evidence was found in the EPG experiments for antixenotic resistance in the resistant cultivar and resistant NIL; however, a possible antibiosis-type resistance could be present but work in a delayed manner, and would therefore not be detected in the short-term EPG experiments as was hypothesized by Sauge et al (2012). Alvarez et al (2006) found similar results for Myzus persicae on Solanum cardiophyllum Lindl.…”
Section: Differences In Virulence Between Populations On Resistant Linesmentioning
confidence: 84%
“…No linkage was found in other herbivorous species, such as Callosobruchus maculatus (southern cowpea weevil; Wasserman and Futuyma 1981), Colias philodice (butterfly; Tabashnik 1986), Papilionidae (swallowtail butterflies; Thompson 1988;Thompson et al 1990), Chrysomelidae (leaf-feeding beetles; Keese 1996), Nilaparvata lugens (brown planthopper; Sezer and Butlin 1998a,b), and Oreina elongata (leaf beetle; Ballabeni and Rahier 2000). However, more recent QTL mapping data for aphids (Hawthorne and Via 2001;Caillaud and Via 2012;Sauge et al 2012), and other genetic association studies in Euphydryas editha (Edith's checkerspot butterfly ;Ng 1988;Singer et al 1988), Liriomyza sativae (leafminer fly; Via 1986), Phyllotreta nemorum (flea beetle; Nielsen 1996), and Papilio glaucus (eastern tiger swallowtail butterfly; Bossart 2003), suggest that some preference and performance alleles can be genetically linked.…”
mentioning
confidence: 99%
“…This hypothesis could be tested in the our own fruit tree-aphid system. Several Prunus genotypes that bear quantitative trait locus of antibiosis resistance against M. persicae are available in the peach germplasm (Sauge et al, 2012).…”
Section: Discussionmentioning
confidence: 99%